Selenothrips rubrocinctus (Thripidae: Panchaetothripinae) under laboratory conditions. - Soto-Rodríguez, Gerardo A (2005)
Selenothrips rubrocinctus (Thripidae: Panchaetothripinae) under laboratory conditions. The tropical thrip Selenothrips rubrocinctus Giard is a polyphagous species sometimes found in commercially important crops that include cocoa and cotton. Laboratory data from specimens collected in Psidium friedrichsthalianum trees in Costa Rica were used to prepare a life table. There was a high mortality in the egg (72.5%) and larva II (18.4%) stages. On leaves, inmature stages presented subvascular distribution and pupae presented submarginal distribution